2014
DOI: 10.1088/0953-8984/27/2/022202
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and structural distortion in BaPt2As2

Abstract: We report the synthesis of BaPt2As2 single crystals and the discovery of superconductivity and a structural phase transition in this compound by measuring the electrical resistivity, magnetic susceptibility and specific heat as well as the x-ray diffraction at low temperatures. BaPt2As2 crystallizes in the CaBe2Ge2-type tetragonal structure (P4/nmm) at room temperature and undergoes a first-order structural transition at TS ≃ 275 K, which is likely to be associated with a charge-density-wave (CDW) instability.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 20 publications
9
26
0
Order By: Relevance
“…This is consistent with optical conductivity results in SrPt 2 As 2 [24] and the quasi-nesting features obtained by band structure calculations in SrPt 2 As 2 [26]. The negative curvature of the electrical resistivity temperature dependence (d 2 ρ/dT 2 < 0) [24,25,20,32,27] indicates strong electron-phonon interaction [34,35,36]. These results suggest that the CDW instability originates from momentum-dependent electron-phonon coupling.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is consistent with optical conductivity results in SrPt 2 As 2 [24] and the quasi-nesting features obtained by band structure calculations in SrPt 2 As 2 [26]. The negative curvature of the electrical resistivity temperature dependence (d 2 ρ/dT 2 < 0) [24,25,20,32,27] indicates strong electron-phonon interaction [34,35,36]. These results suggest that the CDW instability originates from momentum-dependent electron-phonon coupling.…”
Section: Discussionsupporting
confidence: 89%
“…The coexistence of the CDW and superconductivity has been proposed for some of these superconductors: SrPt 2 As 2 , BaPt 2 As 2 and LaPt 2 Si 2 . In these compounds, orthorhombic distortion from the CaBe 2 Ge 2 -type tetragonal structure was observed and associated with the CDW order [19,23,24,25,20,21,32]. SrPt 2 Sb 2 showed a transition from the monoclinic to a modulated orthorhombic structure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, SC is also observed in other 122-type compounds formulated with AT 2 Pn 2 (A = alkaline-earth or rare-earth; T = transition metals; Pn = P, As or Sb) without iron [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. It has been reported that these 122-compounds show a variety of interesting phenomena, such as SC [1], heavy fermion [26], densed Kondo behavior [27], coexistence of SC and anti-ferromagnetism (AFM)/ferromagnetism (FM) /spin-density-wave (SDW) or charge density wave (CDW) [1,13,28].…”
Section: Introductionmentioning
confidence: 98%